2011
DOI: 10.1007/s00044-011-9817-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and biological activities of volatile fractions from three Tunisian cultivars of olive leaves

Abstract: The chemical composition, antibacterial, and antifungal activities of the volatile fractions from fresh and dried leaves of three Olea europaea L. cultivars from Tunisia (Neb jemel, Chemchali and Chemlali) have been studied. The volatile components were obtained via hydrodistillation and analyzed by GC–MS. The major constituents were (E)-3-hexenol, 3-ethenylpyridine, (E)-β-damascenone and phenylethyl alcohol, but their percentages varied according to the treatment of the leaves. Antioxidant activities were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
2
35
1
Order By: Relevance
“…Chemlali and Neb jemel) or ( E )‐3‐hexenol, and phenylethyl alcohol, as well as benzyl alcohol (cv. Chemchali) …”
Section: Resultsmentioning
confidence: 99%
“…Chemlali and Neb jemel) or ( E )‐3‐hexenol, and phenylethyl alcohol, as well as benzyl alcohol (cv. Chemchali) …”
Section: Resultsmentioning
confidence: 99%
“…Their formation is therefore a-Caryophyllene monitored by enzymes and influenced by several important factors, including the cultivar (Brahmi et al, 2012), time of year (Campeol et al, 2003), and region. Therefore, the quantitative and qualitative changes observed in this work are mainly related to cultivar specificities and the harvest time assessed, as the olive trees surveyed were all cultivated in the same olive grove.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on cultivar preference are mainly focused on olive fruits (Malheiro et al, 2015b), rather than olive leaves or the olive tree as a whole. Therefore, studies on olive leaf volatile characterization are scarce, and most are based on hydro-distillate volatile fractions, which are different from the natural emissions (Brahmi et al, 2012;Campeol et al, 2001Campeol et al, , 2003Flamini et al, 2003). Nevertheless, some studies do report the potential effect of olive leaf volatiles in olive fly behavior, and according to Scarpati et al (1993) two abundant olive leaf volatiles, toluene and a-pinene, were the most attractive and repellent cues in olive fly oviposition bioassays, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Works focused on the antimicrobial action of the volatile fraction of pomegranate are absent except this conducted by Mekni et al, (2013b) dealing with pomegranate flowers. Brahmi et al, (2011) suggested that the antimicrobial activity of volatile compounds of leaves of O. europaea is linked to their content in terpenes.…”
Section: Antibacterial Activitymentioning
confidence: 99%